Akibat Hukum Akta Perubahan Yayasan Yang Mengandung Cacat Hukum - Nuanza Uemenina, Hani (Recital Review, 2022)
The deed of change ofÂ Darussalam Maluku Education Foundation was established by a Notary named M. Husain Tuasikal,S.H.,MKn, and was legalized by the Ministry of Law and Human Right of Indonesia. It does not have legal framework because it refers to the Notarial Deed Number:01/2008 dated the 6th of October,2008 which no longer has legal force. Its validity is also objected by the Ministry of Law and Human Rights of the Republic of Indonesia thus, a new foundation is established by changing the name of Darussalam Foundation to Darussalam Maluku Foundation.Â Â The objectives of this research is to discover and to analyze the legal consequence incurred from the drawing up of deed of change of a foundation name before a Notary that may lead to an illegal act. The deed includes the assets possessed by the foundation that is also managed by Darussalam Ambon Foundation and related with the verdict of the supreme court of the Republic of Indonesia Number 404 PK/PDT/2018. It was discovered from the judgeâ€™s consideration that the Notary, in drawing up the deed, has made mistaked as an official and has neglected human right as government that has to make an acknowledgement, to issue a decree, and to analyze judgeâ€™s legal consideration concerning the issuance of deed of change ofÂ foundation, which is supposed to be decided by the owner of the foundation or his heirs; thus, if the owner has passed away, the drawing up of the deed has to be attended by the theirs and the board of patrons of the foundation in relation with the verdict of the supreme court of the Republic of Indonesia Number 404 PK/PDT/2018 Abstrak Akta PerubahanÂ Yayasan Pendidikan Darussalam Maluku yang dibuat oleh Notaris M.Husain Tuasikal,SH.,MKn yang telah disahkan oleh kementrian Hukum dan Hak Asasi Manusia Republik Indonesia tidak mempunyai dasar hukum karena mengacu kepada Akte Notaris Nomor: 01 Tahun 2008 tanggal 6 Oktober 2008 yang sudah tidak mempunyai kekuatan hukum dan pengesahannya telah ditolak oleh Kementrian Hukum dan Hak Asasi Manusia Republik Indonesia,sehingga dibentuk Yayasan baru dari Peralihan nama Yayasan Darussalam dengan nama Yayasan Darussalam Maluku. Tujuan yaitu untuk mengetahui sekaligus menganalisis Akibat Hukum yang ditimbulkan dari Pembuatan Akta Perubahan Yayasan yang dibuat di hadapan notaris yang dapat menimbulkan perbuatan melawan hukum yang di dalamnya terdapat asset-asset yang dimiliki oleh Yayasan yang termasuk pengelolaan Universitas Darussalam Ambon yang dikaitkan dengan Putusan Mahkamah Agung Nomor 404 PK/PDT/2018,mengetahui pertimbangan majelis hakim dalam terjadinya kesalahan atau kelalaian yang dilakukakan Notaris selaku pejabat dalam pembuatan akta dan Hak Asasi Manusia selaku pihak pemerintahan yang memberikan pengakuan dan penerbitan surat keputusan, dan menganalisis pertimbangan hukum majelis hakim tentang pernerbitan akta perubahan yayasan yang harus merupaka suatu keputusan dari pemilik yayasan ataupun Ahli Warisnya,jika pemilik yayasan sudah meninggal dunia dan harus dihadiri oleh Ahli waris,dan Organ Pembina Yayasan yang dikaitkan dengan Putusan Mahkamah Agung Nomor 404 PK/PDT/2018.